1988
DOI: 10.1523/jneurosci.08-06-02172.1988
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of calcium-binding proteins in squid axoplasm

Abstract: The identities and quantities of calcium-binding proteins were determined in axoplasm isolated from the squid giant axon. 45Ca-binding assays on nitrocellulose filters containing axoplasm proteins separated by SDS-polyacrylamide electrophoresis revealed 4 major calcium-binding bands. These included the high-molecular-weight (Mr greater than 330 and 220 X 10(3] neurofilament proteins, an unidentified protein band that migrated around Mr 55,000, and a diverse group of proteins that migrated together around Mr 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 46 publications
1
16
0
2
Order By: Relevance
“…ICa was represented as a uniform influx described by a Hodgkin-Huxley-type formula fitted to a typical record. Ca2" diffused inwardly with binding to the various forms of diazo-4 calculated from our model of photolysis (see Appendix) and to 0-44 mm of an immobile buffer of 4.4 fM affinity, similar to that reported in molluscs (Alema, Calissano, Rusca & Giuditta, 1973;Krinks, Klee, Pant & Gainer, 1988) and identical to singly photolysed diazo-4 to simplify calculations. Ca2" was extruded by uptake into organelles and a surface membrane pump adjusted to match experimental measurements (Smith & Zucker, 1980).…”
Section: Predicting Effects Of Diazo-4 Photolysis With a 'Shell' Modelmentioning
confidence: 72%
See 1 more Smart Citation
“…ICa was represented as a uniform influx described by a Hodgkin-Huxley-type formula fitted to a typical record. Ca2" diffused inwardly with binding to the various forms of diazo-4 calculated from our model of photolysis (see Appendix) and to 0-44 mm of an immobile buffer of 4.4 fM affinity, similar to that reported in molluscs (Alema, Calissano, Rusca & Giuditta, 1973;Krinks, Klee, Pant & Gainer, 1988) and identical to singly photolysed diazo-4 to simplify calculations. Ca2" was extruded by uptake into organelles and a surface membrane pump adjusted to match experimental measurements (Smith & Zucker, 1980).…”
Section: Predicting Effects Of Diazo-4 Photolysis With a 'Shell' Modelmentioning
confidence: 72%
“…For a native buffer, we assumed an initial concentration of 1 mm, a binding constant of 108 M-l s-' and a dissociation rate of 2000 s-1, yielding a dissociation constant of 20 #M. The binding parameters match the quantity and buffering capacity of cytoplasmic buffer measured in molluscan neurons (Smith & Zucker, 1980;Krinks et al 1988); a fast binding rate is assumed by analogy with T-sites of Ca2+-binding protein in muscle (Robertson, Johnson & Potter, 1981), and because transients of unbuffered [Ca2+]i are not observed to brief Ca2+ influx, even on a millisecond time scale (Charlton, Smith & Zucker, 1982). A diffusion constant of 10-7 cm2 S-1 was assumed, appropriate for a large protein.…”
Section: Implications Of the Results With Nitr-5 And Dm-nitrophenmentioning
confidence: 99%
“…Comparative Southern blot analyses using all three AtCBL cDNAs as probes (Fig. 2) instead of EGTA (27). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins were stained with Coomassie blue to monitor the mobility pattern of the proteins. For the 45 Ca 2ϩ -overlay assay, recombinant proteins were analyzed by SDS͞PAGE, transferred to nitrocellulose membrane, and blotted by 45 Ca 2ϩ as previously described (27).…”
Section: Methodsmentioning
confidence: 99%
“…We performed dose-dependent analysis of cyclosporine A to verify the neurofilament phosphorylation and observed no effect on perikaryal phosphorylation of NF. In previous studies using the squid giant axon system, we have shown that PP2B is abundant in the axons compared with cell bodies (Krinks et al, 1988). PP2B levels and activity are shown to be increased in AD brain (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 74%